The Influence Of Menopausal Indicators And Family Support On The Well-Being Of Women With Menopause - Ramyashree S; Jacintha Veigas; Sudhir Prabhu; Shishir Kumar (Annals of Abbasi Shaheed Hospital and Karachi Medical & Dental College)
Objective: The focus of the study was to ascertain the relationship between menopausal women’s physical and mental well-being, the intensity of their menopausal symptoms, and their family support. The study also aimed to find the impact of menopausal symptoms and family support on the well-being of women during menopausal age. Methods: A cross-sectional design of 450 menopausal women participated in the study. The standardized menopausal symptom rating scale the well-being assessment instrument was used. The duration of the study was from October 2020 to December 2021. A systematic family support questionnaire was used to evaluate family support. The SPSS software version 16 was utilized for the data analysis. Results: The average age of women was 49.8 years with an 8.6 standard deviation. A significant portion of women reported challenges, with 51% experiencing sleep disturbances, including trouble sleeping and early waking. Other symptoms included confusion (32%), muscle and joint pain (30%), restlessness (22%), sadness (45%), urinary issues (7%), reduced sexual desire (20%), and joint discomfort (30%). Additionally, 51.3% of participants reported inadequate familial support, while 32.6% indicated poor mental well-being. In contrast, 32.5% of women were moderately satisfied with family support. The study revealed a strong positive correlation between family support and well-being, with an rvalue of 0.625 and a statistically significant p-value of 0.012 (p < 0.05). An ANOVA test showed that familial support significantly affects symptom severity associated with menopause, with an F-value of 1.8 and p 0.001. Furthermore, a strong association was found between women’s well-being and certain demographic factors, notably family income, with a p-value of 0.02, indicating statistical significance. Conclusion: The investigation has determined that a large number of women in rural areas struggle with menopausal symptoms that affect their physiologic and psychological processes as they age. Family support is the major component that will affect women’s life as they are in menopause.